Pengaruh Profitabilitas dan Penghindaran Pajak Terhadap Pendanaan Eksternal pada Perusahaan Sektor Asuransi - ihsan abdullah (Jurnal Riset AKuntansi dan Bisnis, 2020)
This study aims to see the effect of Profitability and Tax Avoidance on External Funding in companies listed on the IDX in the Insurance sub-sector. The method used in this research is descriptive quantitative research that seeks to examine and explain how an independent variable affects the dependent variable. Population Population and sample in this study as many as 13 trading companies but only 6 companies provide complete financial reports. 5 year observation period from 2015-2019 using annual financial reports, so that a total sample of 30 observations of data collection in this study is to use documentation data with the type and source of quantitative data obtained from www.idx.co.id. The data analysis technique used is multiple linear regression analysis. Based on the test results it shows that Profitability has an effect on External Funding, Tax Avoidance has an effect on External Funding. But simultaneously Profitability and Tax Avoidance have an effect on External Funding.simultan Profitabilitas dan Penghindaran Pajak berpengaruh terhadap Pendanaan Eksternal.